Flood Risk Assessment Using Hydrological Model in the Xe Bangfai Basin, Mahaxay District, Khammuane Province - Souphome In, Outhikone (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
Mahaxay district, Khammouane province is affected by floods almost every year and has caused huge losses to people's livelihoodsin terms of housing and agriculture, as it locates in the Xe Bang Fai sub-basin, which is one of the eight Mekong tributaries with high risk of flooding according to the National Disaster Risk Report, 2010 of the Ministry of Natural Resources and Environment. Therefore, this study aims to: 1) To analyze the water inflow into the Xe Bang Fai sub-catchment in Mahaxay district (using rainfall data in 2000, 2004, 2005, 2011, 2013, 2015) and 2) To estimate the extent of the flood area according to 6 return period (2, 5, 10, 25, 50 and 100 years). The results of the study show that: HEC-HMS model can simulate the water flow into the Xe Bang Fai sub-basin quite well based on the model accuracy index values ​​of R2 = 0.78 and NSE = 0.67. In September 2000, the maximum average flow rate was 1,961 m3/s, September 2004 was 1,835 m3/s, August 2005 was 2,812 m3/s, August 2011 was 2,618 m3/s, August 2013 was 1,598 m3/s, and August 2015 was 1,870 m3/s. On average, the maximum flow rate occurs between August and September of each year. The flood area in each cycle in the following order: 2 years will have a flood area of ​​5,169 hectares, 5 years will have 6,021 hectares, 10 years will have 6,216 hectares, 25 years will have 6,424 hectares, 50 years will have 7,050 hectares and 100 years will have 7,198 hectares, covering about 18 to 22 villages with a depth ranging from 30 centimeters to more than 3 meters. This study is in line with the results of the National Disaster Risk Assessment Report, 2010, which has about 14 villages at risk of flooding in Mahaxay District.